TOPOGRAPHIC IMAGING OF MYCOBACTERIUM SMEGMATIS CELLS SURFACE TREATED WITH ETHAMBUTOL AND RIFAMPICIN - P. SANKAR GANESH; K. KANIVALAN; K. RAJENDRAN; D.KUMAR; S. KUMARAN (International Journal of Pharma and Bio Sciences, 2013)
The mycobacterial cells were treated with 0.96 mg/ml of Ethambutol (EMB) and 0.64 mg/ml of Rifampicin (RIF) in Luria Bertani (LB) broth. The native and treated cells were serially diluted (10-1 to 10-30), from the 10-25 dilution native cells and antibiotics treated cells were imaged using Atomic Force Microscopy (AFM). The normal surface roughness (Rrms) of the native cells was 0.353 nm, whereas the surface roughness for EMB treated cells was 3.14 nm. The RIF treated cells pores (width size: 19.86 nm) were created on the surface of the cell membrane. This paper provides a new finding on EMB was alone creates the roughness on the cell wall surface of Mycobacterium smegmatis. Interestingly we got the better image of after treatment of RIF was creates pores on the cell wall surface of M. smegmatis.